FINANCIAL BUSINESS FEASIBILITY BIOMEDICAL IMPLANT PRODUCTION - Handaru Setiawan, Suganta
The market size of medical implant in Indonesia is estimated around US$ 20 million in 2021 and will reach a value US$ 36,67 million by 2026 with 15.2% CAGR. Furthermore, the total medical implant market size in Asia was estimated US$ 7.302 million and is expected to growth become US$ 10,610 million in 2026. Those number bring medical implant business become very attractive market potential to be developed and produced in Indonesia, to meet local demand as well as to penetrate Asia market. PT. Langit Biru is global manufacturing & technology company with core business in producing steel materials for various industry segment that have plan to make investment project in biomedical implant production using additive manufacturing process to grab the attractive market potential of biomedical implant and to diversify the business footprint in medical segment. The feasibility study is carried out by analyzing the business situation using PESTEL, VRIO, SWOT and risk analysis. Furthermore, financial feasibility is analyzed using capital budgeting method that consist of, net present value (NPV), internal rate of return (IRR), payback period (PP) and profitability index (PI). Based on the analysis, the project is feasible and accepted with the result NPV USD 5.279.985 , IRR 35%, profitability index 3.3 and payback period 3,7 years. Sensitivity analysis also reveals that this project exhibits a relatively low susceptibility to input variables where NPV is still positive when subjected to variable changes. In the worst-case scenario analysis, it is observed that the investment project is still feasible where NPV is positive with value USD 852.372 (84% lower than the base case), IRR is 15% and it is still bigger than WACC 9,66%. Lastly Montecarlo simulation expose that the project has 100% probability of positive NPV from 1000 simulation with NPV mean USD 5.223.985 that very close to the base NPV (-1.06% lower).